Um olhar bakhtiniano para o uso das tecnologias digitais na formação docente - Soares, Terezinha Gorete Vilela (2019)
This research has as objective to investigate as if of the a formation of the teacher as for the work with the digital technologies and to consider some principles for a proposal of education of these technologies to the light of the reflections of Bakhtin and its Circle. For this, it is concentrated in the characterization of a normative official document as a sort of the speech and in the verification in the way as if they stop in it the dialogical relations for the considered subject. Its methodology is of qualitative and bibliographical matrix. Our inquiry was oriented for the methodological perspective of Bakhtin and its Circle, supported in the ample conception of statements, discursive sorts, spheres and dialogism, as well as in the works of its commentators, such as: Faraco (2009), Brait (2005; 2016; 2017), Grillo (2016), Marchezan (2016), Fiorin (2017), among others studious authors of the teacher formation and the use of technologies. Our object of study it constituted of the analysis of Resolution CNE/CP nº 2/2015, 1º of July of 2015, produced and approved by full advice (CP) of the National Advice of Education (CNE) in accord with the Ministry of Education (MEC), that it defines the directive curricular national (DCNs) for the teacher initial formation in superior level and the use of the digital technologies. He investigated himself, in this document, if the digital technologies must be inserted in the context of the teaching formation in superior education and if the future teacher must leave prepared to mediate a productive work with them. Thus, one evidenced that the DCNs corresponds to an official document, therefore it is part of a normative discursive sort and to the classification of the secondary sorts. The discourse of the Resolution reflects and refracts to the voice of one high educational public sphere (MEC/CNE/CP), as well as, it circulates and it is consumed in the educational spheres of teaching and pertaining to school formation. The voices of the authors are of active subject in the speech, that when enunciating, if they direct its interlocutors, who are the Institutions of upper education (IES), and to the subjects in formation teacher and school. The enunciative context of Resolution CNE/CP nº 2/2015 assumes the role to form professors for an education of quality and contemporary, therefore the concern for parts of the enunciators exists in diverse points of the statement on the implantation of the resources of the technologies types in formation environments. Although not to have the obligatoriness of the use of the resources of the technologies in the resume, which had the curricular relaxation and the autonomy of the IES, are evidenced the necessity of its integration and actual application in the educational contexts.